Optimization of Digital Marketing Training for Bazaf Supermarket to Empower Productive Waqf - Bulan, Rachima Annisa; Ninda Ardiani; Ruslianor Maika; Satrio Sudarso; Raisha Salisa (Institut Agama Islam Negeri Ponorogo, 2025)
The shift from conventional to digital marketing presents significant opportunities for small business development, including productive waqf-based enterprises. However, limited digital literacy remains a major barrier for effective implementation. This community service program aimed to strengthen the digital marketing capacity of productive waqf business units under the Bina Peradaban Islam Indonesia Foundation, with a particular focus on Bazaf Supermarket. The program employed a descriptive qualitative approach through four stages: problem identification, socialization, training, and mentoring. Data were collected using observations, interviews, documentation, and pre- and post-tests to assess changes in participants’ understanding and skills. The results indicate a notable improvement in participants’ digital marketing knowledge and practical abilities, particularly in utilizing WhatsApp Business for product promotion and customer engagement. Following the intervention, Bazaf Supermarket successfully implemented digital marketing strategies, which contributed to increased customer inquiries and sales performance. These findings demonstrate that structured digital marketing training and mentoring can effectively enhance the operational capacity of productive waqf business units. This program provides practical implications for community-based economic empowerment initiatives, highlighting digital marketing as a strategic tool to strengthen the sustainability and social impact of productive waqf enterprises